Neurostructural traces of early life adversities: a meta-analysis exploring age- and adversity-specific effects - Pollok, Tania; Kaiser, Anna; Kraaijenvanger, Eline J.; Monninger, Maximilian; Brandeis, Daniel; Banaschewski, Tobias; Eickhoff, Simon B.; Holz, Nathalie E. (Neuroscience & biobehavioral reviews, 2022)
Early life adversities (ELAs) are associated with an increased risk of psychopathology, with studies suggesting a relation to structural brain alterations. Given the recently growing evidence of ELA effects on brain structure, an updated summary is highly warranted. Therefore, anatomical likelihood estimation was used to conduct a coordinate-based meta-analysis of gray matter volume (GMV) alterations associated with ELAs, including sub-analyses for different age groups and maltreatment as specific ELA-type. The analyses uncovered a convergence of pooled ELA-effects on GMV in the right hippocampus and amygdala and the left inferior frontal gyrus, age-specific effects for the right amygdala and hippocampus in children and adolescents, and maltreatment-specific effects for the right perigenual anterior cingulate cortex in adults. These results reveal a possible underlying commonality in the impact of adversity and also point to specific age and maltreatment effects. They suggest neural markers of ELAs in regions involved in socio-emotional functioning and stress regulation, with the potential to be used as targets for interventions designed to buffer or reverse harmful ELA-effects.
Gesehen am 30.08.2022